SIFAT-FK RUANG BARISAN CESARO ORLICZ - Haryadi, Haryadi - (EPSILON: JURNAL MATEMATIKA MURNI DAN TERAPAN (EPSILON: JOURNAL OF PURE AND APPLIED MATHEMATICS), 2024)
The Cesaro sequence space , ( , which is the FK-space, has been generalized to the Cesaro-Orlicz sequence space . This prompted the study of several properties in  that have been known in . In this paper, the properties of completeness and FK-properties in the Cesaro-Orlicz space are discussed. For this discussion, a modular approach is used. The results of the study show that the space   is a convex modular space. This sequence space is also complete to the Luxemburg norm and has K-properties. Furthermore, this space is a BK-space. These results can be used to study the Kothe-Toeplitz dual, which is an important part of the transformation of the infinite matrix